2012
DOI: 10.1371/journal.pone.0047972
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Neuroglobin Reveals Its Early Origins

Abstract: BackgroundNeuroglobin (Ngb) is a hexacoordinated globin expressed mainly in the central and peripheral nervous system of vertebrates. Although several hypotheses have been put forward regarding the role of neuroglobin, its definite function remains uncertain. Ngb appears to have a neuro-protective role enhancing cell viability under hypoxia and other types of oxidative stress. Ngb is phylogenetically ancient and has a substitution rate nearly four times lower than that of other vertebrate globins, e.g. hemoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 128 publications
0
12
0
Order By: Relevance
“…Predictive analysis of the consensus sequences that can be recognized by various TFs in NGB promoter was already reported and some TFs have been experimentally validated by chromatin immunoprecipitation, for example, NFkB and Sp1 . Figure shows the results we obtained using matrix‐scan algorithms (Jaspar CORE 2009, NHRScan) reported in top and bottom panels, respectively.…”
mentioning
confidence: 86%
“…Predictive analysis of the consensus sequences that can be recognized by various TFs in NGB promoter was already reported and some TFs have been experimentally validated by chromatin immunoprecipitation, for example, NFkB and Sp1 . Figure shows the results we obtained using matrix‐scan algorithms (Jaspar CORE 2009, NHRScan) reported in top and bottom panels, respectively.…”
mentioning
confidence: 86%
“…Despite its early evolutionary origins and strong sequence and structure conservation [2], its precise function is not well understood [3]. Neuroglobin (Ngb) has been implicated in several paradigms of neuroprotection, involving improved oxygen homeostasis, oxygen sensing, neutralization of free radicals, redox cycling [4, 5, 6, 7, 8, 9], as well as neuron type-specific regulatory functions [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Many phylogenetic studies have focused on the hemoglobins of Mammals and Vertebrates in general, starting with the seminal work of Zuckerkandl and Pauling (1962). A smaller number of studies have focused on the evolution of Metazoan globins (4)(5)(6)(7). These studies have shown that Vertebrate hemoglobins and the related myoglobins are only a small branch in a vast tree of animal globins, some of which are used for respiratory functions but many others have still unknown functions.…”
Section: Introductionmentioning
confidence: 99%